Performance and Determinants of Organic Rice Agribusiness Systems: Evidence from Lampung Province Using PLS-SEM - Sri Handayani; Wan Abbas Zakaria; Novi Rosanti; Hamim Sudarsono; Dwi Haryono (Universitas Panji Sakti, 2026)
The performance of agribusiness is linked to the sustainability of organic rice agribusinesses in Lampung Province. This study enriches agribusiness system theory by validating the integration model of subsystems as the main determinant for optimizing the performance of organic rice agribusiness. This study aims to analyze the performance of the organic rice agribusiness system and the factors that determine organic rice agribusiness in Lampung Province. The research was conducted in four districts that implement organic rice farming: South Lampung, East Lampung, Central Lampung, and Pringsewu. The number of respondents was 50 organic rice farmers. Agribusiness performance analysis was measured using a performance index with a percentage ratio calculation between the total actual score and the maximum score to be classified into five categories of performance assessment interval scale. The determinants of agribusiness performance were analyzed using partial least squares structural equation modeling (PLS-SEM). The results show that the organic rice agribusiness system showed good performance. Meanwhile, the marketing subsystem is fair, with a performance score of 2.96. Overall, the organic rice agribusiness system showed good performance, with a score of 3.63 or 72.7%. The results of the second analysis indicate that the agribusiness subsystems consisting of the production inputs, farming, post-harvest, marketing, and supporting element subsystems affect the sustainability of organic rice agribusiness. Strengthening market institutions into business units (cooperatives) can serve as aggregators that consolidate harvests in terms of both quantity and quality. This will create economies of scale and improve farmers' bargaining power.